Protection of the Rights of Children Born Outside of Marriage in Constitutional Court Decision No. 46/PUU-VIII/2010 Reviewed from the Perspective of the Imam Shafi'i School of Law - Aulia Nurazizah; Sinta Devi Ambarwati; Tiara Yuliarsih (al-Afkar, Journal For Islamic Studies, 2025)
Marriage serves as a means to establish a legitimate relationship, both religiously and legally, aiming to achieve domestic harmony and offspring. It also intends to preserve the purity of lineage, preventing adultery and its potential impact on descendants and their rights. Constitutional Court Decision No. 46/PUU-VIII/2010 stipulates that children born outside of a legal marriage possess the same rights as those born within one. However, according to the Imam Shafi'i school of thought, children born outside of a legal marriage do not receive the same rights as children born within a legal marriage. This research aims to examine and compare the positive legal policy of the Constitutional Court's decision with the policies proposed by the Imam Shafi'i school of thought. This study employs a normative legal research method, utilizing a library research approach to gather data from various primary and secondary sources. The data analysis method used is descriptive analysis with deductive conclusions. The findings of this research reveal data in the form of the verdict of Constitutional Court Decision No. 46/PUU-VIII/2010, the perspective of the Imam Shafi'i school of thought, findings regarding the recognition of a child's status, and findings concerning the protection of the rights of children born out of wedlock. The data analysis yields results in the form of the concept of child protection according to Constitutional Court Decision No. 46/PUU-VIII/2010 and the Imam Shafi'i school of thought. Furthermore, the research presents findings regarding the legal consequences of the discrepancy between the concept of protecting the rights of children born out of wedlock in Constitutional Court Decision No. 46/PUU-VIII/2010 and the viewpoint of the Imam Shafi'i school of thought.